Assessing the Effect of Plant Clinic Services on Agricultural Practices in Mukono District, Uganda. A Case Study in Ntawo Sub County - Hillary Byaruhanga (Uganda Christian University, 2025)
This study investigates the effect of plant clinic services on agricultural practices among smallholder farmers in Ntawo Sub County, Mukono District, Uganda. Given that agriculture remains the backbone of Uganda’s economy, yet productivity is hampered by persistent pest infestations and plant diseases, innovative extension approaches such as plant clinics have been introduced to enhance early diagnosis and pest management practices. The primary objective of this research was to evaluate how these services influence farmers’ knowledge, skills, and overall perceptions regarding pest and disease management, thereby contributing to improved crop health and productivity. A mixed-methods research design was employed, combining quantitative data from structured questionnaires with qualitative insights obtained through faceto-face interviews. A total of 73 farmers were randomly selected based on a sample derived from the Morgan table. The instrument covered key aspects including demographic profiles, perception of service quality, satisfaction levels, and the self-reported improvement in agricultural practices after exposure to plant clinic services. Data analysis was performed using descriptive statistics, t-tests to compare knowledge levels between users and non-users, and chi-square tests to examine the relationships between service quality and perceived importance. The findings revealed a predominantly positive perception of plant clinic services. The majority of respondents rated the quality of services as ―Good‖ or ―Very Good‖ and acknowledged the high importance of these services for effective pest and disease management. Notably, a significant improvement in knowledge and skills was observed among farmers who accessed plant clinic services compared to non-users. Statistical analysis indicated a substantial difference (t = 11.43, p < 0.001) in knowledge levels, with clinic users demonstrating higher proficiency and confidence in managing crop health challenges. Moreover, increased confidence in the application of integrated pest management strategies was reported, suggesting that plant clinics serve not only as diagnostic centers but also as critical hubs for agricultural education and empowerment. Based on these results, the study recommends an expansion of plant clinic services to other sub counties within Mukono District and beyond. Enhancing outreach through mobile-based advisory systems and hands-on follow-up demonstrations could further strengthen the impact of these services. Overall, the research underscores the vital role of plant clinics in promoting sustainable agricultural practices and supporting smallholder farmers in overcoming pest and disease challenges, thereby contributing to improved food security and rural development in Uganda.